Attitude as Subjective Opinion in the Evaluative Language of Malay Newspaper Discourse - Sarikon, Suhaini; Abdullah, Roksana Bibi (LingPoet: Journal of Linguistics and Literary Research, 2025)
This article is based on a study that advances the concept of Attitude as subjective opinion within Evaluative Language Theory. This concept is also applied in Malay newspaper discourse. Two types of newspapers were used in this study: Berita Harian/Berita Minggu Singapura (BH/BM S’pura) and Berita Harian/Berita Ahad Malaysia (BH/BA M’sia). Only commentary articles were selected as study materials, ensuring they were related to the bombing of the World Trade Center in New York that occurred on September 11, 2001. This study is limited to articles with such themes due to their similar context. The study explores the strategies employed by newspapers through their commentators to influence readers, enabling the newspapers to instill the propositions they aim to advance within the readers. This description is based on analytical findings regarding Attitude in Malay newspaper discourse contained within the texts. The study is grounded in Systemic-Functional Linguistics as a linguistic framework for examining the Attitude present in Malay language newspaper discourse. Attitude consists of types such as Affect, Judgement, and Appreciation. The concept of Evaluative Language in Malay newspaper discourse can be explained by outlining these types of Attitude.